Hubungan Berat dan Penggunaan Tas Sekolah dengan keluhan Musculoskeletar Disorders (MSDs) pada Anak Usia Sekolah Dasar 7 – 12 Tahun - A Abdurrachman; Anang Prasetya; Lutfi Faradila (Jurnal Ilmiah Kesehatan, 2024)
MSDs are a collection of symptoms and disorders related to muscle tissue, tendons, ligaments, cartilage, nervous system, bone structure and blood vessels. In Indonesia, MSDs tend to appear in school-age children due to immature bone development, so bad habits have an impact on body development. The use of bags is something that is often a topic of problems related to musculoskeletal complaints. This study aims to find the relationship between bag weight and duration of use and musculoskeletal disorders in elementary school children aged 7 - 12 years. This type of research is descriptive with a cross sectional design. The sample was 60 children aged 7 - 12 years who were selected using proportional random sampling. This research was conducted in May – September 2023 in the Tangkil Kulon Kedungwuni Village Area. The results of research from 60 respondents showed that there was a significant relationship between the weight of the bag and LMA and MSDs in children aged 7 - 12 years (p value = 0.001, p value < 0.05), there was a significant relationship between the length of use of the bag and pain problems. musculoskeletal in children aged 7 – 12 years (p value = 0.000, p value < 0.05). The conclusion is that the weight of the bag and the length of time using the bag have a significant relationship with MSDs in school aged children aged 7 - 12 years. Which means that the heavier and longer the child uses the bag, the greater the MSDs complaints they will experience.